Water for a changing world : developing local knowledge and capacity : proceedings of the International Symposium Water for a Changing World–Developing Local Knowledge and Capacity, Delft, the Netherlands, June 13-15, 2007 /: developing local knowledge and capacity : proceedings of the International Symposium Water for a Changing World–Developing Local Knowledge and Capacity, Delft, the Netherlands, June 13-15, 2007. (©2009) - Unknown
No abstract available